Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


3 x^{2} -2√6x+2=0
3 x^{2} -√6x-√6x+2=0
√3 x^{2} *√3 x^{2} -√3x*√2x-√3x*√2x+√2*√2=0
Therefore the equation has two equal roots; √2/√3
0 0 0
I hope it really helped u!! If it did plz mark as the brainliest
3x^2-√6x-√6x+2=0 √3x(√3x-√2)-√2(√3x-√2)=0 (√3x-√2)(√3x-√2)=0 x=√2/√3 and x=√2/√3
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts